1991
DOI: 10.1007/bf03032685
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report on the intervention trials of primary liver cancer in high-risk populations with nutritional supplementation of selenium in China

Abstract: The purpose of this study was to evaluate the effect of selenium (Se) in the prevention of human primary liver cancer. Three intervention trials were conducted among the residents at high risk to primary liver cancer (PLC) in Qidong county, Jiang-su province, the People's Republic of China. This area has the second highest rate of PLC in China. One trial was undertaken among the general population in a township with supplement of table salt fortified with 15 ppm anhydrous sodium selenite (Se-salt) for 5 y and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 5 publications
0
60
0
1
Order By: Relevance
“…Sharp et al reported a reduced risk of HCC in Japanese atomic bomb survivors with frequent soya food consumption (Sharp et al, 2005). The relation between some nutrients intake and HCC risk were investigated, among which favorable effect were reported including flavonoid (Lagiou et al, 2008), β-carotene (Polesel et al, 2007), retinoids (Yuan et al, 2006), selenium (Yu et al, 1991), etc.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Sharp et al reported a reduced risk of HCC in Japanese atomic bomb survivors with frequent soya food consumption (Sharp et al, 2005). The relation between some nutrients intake and HCC risk were investigated, among which favorable effect were reported including flavonoid (Lagiou et al, 2008), β-carotene (Polesel et al, 2007), retinoids (Yuan et al, 2006), selenium (Yu et al, 1991), etc.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…In 2 Chinese trials, selenium decreased liver cancer incidence in patients at high risk because of either a family history of liver cancer or hepatitis B exposure status (20). The reports of these trials, however, lack many important details.…”
Section: Seleniummentioning
confidence: 99%
“…Chemoprevention trials have been carried out in regions of China with a high incidence of hepatocellular carcinoma due to high incidence of hepatitis B combined with high aflatoxin contamination of food. The incidence of cancer was decreased by 35% in selenium-salt-supplemented group (346). However, because the health and environmental insults are radically different in China compared with those in the westernized world, the conclusions from this trial cannot be interpreted as universal.…”
Section: Organoselenium Compounds and Selenoproteins As Potentialmentioning
confidence: 86%